EVALUATION OF BIOGENIC LIMESTONES FROM HERETHIANA AREA IN WESTERN CRETE FOR HYDRAULIC LIME PRODUCTION - Μαρκόπουλος Θ.; Τριανταφύλλου Γ.; Μανούσογλου Ε. (Bulletin of the Geological Society of Greece, 2004)
Biogenic limestones from the area of Herethiana, Western Crete, have been examined in order to evaluate their properties as hydraulic lime raw materials. Samples of three different horizons, X1, X2, and X3 have been investigated using X -ray diffraction (XRD), X - ray fluorescence spectroscopy (XRF), optical and scanning electron microscopy (SEM) and calcimetry analyses. According to the XRD analyses the main component is calcite variying between 80% and 84%. Illite, quartz, albite and goethite are also present in minor amounts. Representative samples, with a particular grain size of the different horizons, were burned at 900°C for 12 hours, to produce hydraulic lime. The analysis of the calcined products showed that larnite, portlandite and lime appear in all samples. Quartz and hematite are also present in minor amounts. The abundance of amorphous silica in the form of silica sponges and diatoms offers the necessary active silica to form, together with an appropriate portion of free lime, the calcium-silicate phase, which is present in all samples in adequate percentages. According to the European standards of the building limes the calcined products of the materials of the three different horizons can be classified as feebly, moderate and eminently hydraulic limes